Social seed networks and climate change adaptation in East Africa - Zebroski, W.M.; Lacasse, H.K.; Otieno, G.; Reynolds, Travis W.; Lavalle, N.; Baker-Wacks, E.; Klein, E. (2018)
Our study investigates the routes of information flow through which smallholder exchange seed and information. We then examine how these exchanges among farmer networks can be improved. In order to examine the characteristics of these networks, our study analyzed household-level survey data collected by Bioversity International from sites in Kenya, Uganda, and Tanzania. Current seed sources and climate adaptation strategies were determined by creating summary statistics from the survey data. UCINET network analyses were conducted to acquire a more specific understanding of the current social networks among farmers. Seed networks were categorized by country, gender, and crop and then analyzed to determine where the distribution of seed and information can be improved and utilized.